2014
DOI: 10.1063/1.4864020
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous distribution of defect-related emission in Si-doped AlGaN epitaxial layers with different Al content and Si concentration

Abstract: The spatial distribution of luminescence in Si-doped AlGaN epitaxial layers that differ in Al content and Si concentration has been studied by cathodoluminescence (CL) mapping in combination with scanning electron microscopy. The density of surface hillocks increased with decreasing Al content and with increasing Si concentration. The mechanisms giving rise to those hillocks are likely different. The hillocks induced surface roughening, and the compositional fluctuation and local donor-acceptor-pair (DAP) emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The three major factors affecting the blue shift in the band gap of the semiconductor nanomaterials are quantum confinement effect, , lowering temperature of the material, and alloying with appropriate elements. It is reported that the exciton Bohr radius for GaN is 11 nm, so any role of the quantum confinement effect in elevating the band gap for as-prepared AlGaN NWs to 3.55 eV with an average diameter 50–100 nm can be ruled out. The reported band gap of GaN is 3.503 eV at 0 K. , Thus, the free exciton emission at 3.55 eV strongly confirms the presence of Al in the as-prepared NW sample (Figure ). The temperature-dependent study shows blue shift of the band gap with decreasing temperature (Supporting Information Figure S5).…”
Section: Resultssupporting
confidence: 56%
“…The three major factors affecting the blue shift in the band gap of the semiconductor nanomaterials are quantum confinement effect, , lowering temperature of the material, and alloying with appropriate elements. It is reported that the exciton Bohr radius for GaN is 11 nm, so any role of the quantum confinement effect in elevating the band gap for as-prepared AlGaN NWs to 3.55 eV with an average diameter 50–100 nm can be ruled out. The reported band gap of GaN is 3.503 eV at 0 K. , Thus, the free exciton emission at 3.55 eV strongly confirms the presence of Al in the as-prepared NW sample (Figure ). The temperature-dependent study shows blue shift of the band gap with decreasing temperature (Supporting Information Figure S5).…”
Section: Resultssupporting
confidence: 56%
“…Considering the atomically smooth surface as well as the low TDD in the ELO-AlN(a) template, this behavior might be explained by strain relaxation in thick Al 0.5 Ga 0.5 N layers through enhanced surface corrugation (transition to threedimensional (3D) growth). A similar effect has been frequently observed in AlGaN layers with increasing Ga content grown on planar AlN [25,26], where increasing compressive strain can be relaxed either through formation of additional dislocations and dislocation inclination (preferably for AlGaN with high Al content [24,27,28]) or through an enhanced surface roughening (preferably for low Al contents [25,26]). It should be emphasized that in our experiment we have applied the same deposition conditions for Al 0.5 Ga 0.5 N growth on both ELO-AlN(a) and ELO-AlN(m) templates.…”
Section: Defect Distribution In Al X Ga 1 à X N Layers On Elo-aln(a)mentioning
confidence: 63%
“…The high linewidths for the AlGaN samples are mainly based on bandgap fluctuations caused by the statistical distribution of group‐III atoms and the small exciton radius in AlGaN. [ 31,32 ] In addition, the AlGaN composition can vary at certain growth features like growth islands, [ 33 ] hillocks, [ 34 ] or growth steps. [ 35,36 ] The latter effects are rarely present in sample C, but add to the broader emission linewidth in sample D, where the studied AlGaN layer is grown under a higher compressive strain.…”
Section: Resultsmentioning
confidence: 99%